Europe and Global Imbalances - Lane, Philip (IMF Working Papers; Working Paper ;, 2007)
Although Europe in the aggregate is a not a major contributor to global current account imbalances, its trade and financial linkages with the rest of the world mean that it will still be affected by a shift in the current configuration of external deficits and surpluses. We assess the macroeconomic impact on Europe of global current account adjustment under alternative scenarios, emphasizing both trade and financial channels. Finally, we consider heterogeneous exposure across individual European economies to external adjustment shocks.